Acute exercise reduces feeding by activating IL-6/Tubby axis in the mouse hypothalamus - de Oliveira Micheletti, Thayana; Cassia dos Santos, Andressa; Rocha, Guilherme Zweig; Silva, Vagner Ramon Rodrigues; Quaresma, Paula Gabriele Fernandes; Assalin, Heloisa Balan; Junqueira, Felipe Silva; Ropelle, Eduardo Rochete; Oliveira, Alexandre Gabarra; Saad, Mario Jose Abdalla; Prada, Patricia de Oliveira (Frontiers in Physiology, 2022)
Background: Acute exercise contributes to decreasing feeding through leptin and interleukin/Janus kinase 2/ signal transducers and activators of transcription 3 (IL-6/JAK2/ STAT3) signaling. Considering the pleiotropic use of substrates by JAK2, and that the Tubby protein (TUB) can be phosphorylated by JAK2 in CHO-IR cells; we speculate that acute exercise can activate the IL-6/JAK2/TUB pathway to decrease food intake. Aims: We aim to investigate whether acute exercise induces tyrosine phosphorylation and the association of TUB and JAK2 in the hypothalamus and if IL-6 is involved in this response; furthermore, whether the IL-6/TUB axis is increased by the acute exercise regulates feeding, and if leptin has an additive effect over this mechanism. Methods: We employed a combination of genetic, pharmacological, and molecular approaches for these purposes. Key findings: In vivo experiments showed that acute exercise increased the tyrosine phosphorylation and association of JAK2/TUB in the hypothalamus, which reduced feeding; this response was dependent on IL-6. Leptin had no additive effect on this mechanism. Significance: This study suggests a novel hypothalamic pathway by which IL-6 released by exercise regulates feeding.